2015
DOI: 10.1155/2015/170427
|View full text |Cite
|
Sign up to set email alerts
|

Generation of a Fibrin Based Three-Layered Skin Substitute

Abstract: A variety of skin substitutes that restore epidermal and dermal structures are currently available on the market. However, the main focus in research and clinical application lies on dermal and epidermal substitutes whereas the development of a subcutaneous replacement (hypodermis) is often disregarded. In this study we used fibrin sealant as hydrogel scaffold to generate a three-layered skin substitute. For the hypodermal layer adipose-derived stem cells (ASCs) and mature adipocytes were embedded in the fibri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 25 publications
0
30
0
Order By: Relevance
“…Piccinno et al (2013) and Kober et al (2015) have shown that ASCs enhance adipocyte cell survival. 31 , 32 …”
Section: Discussionmentioning
confidence: 99%
“…Piccinno et al (2013) and Kober et al (2015) have shown that ASCs enhance adipocyte cell survival. 31 , 32 …”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have mainly used single hydrogel‐type materials as scaffolds such as a collagen–elastin matrix (Keck et al, ), fibrin hydrogel (Kober, Gugerell, Schmid, Kamolz, & Keck, ), human plasma hydrogel (Monfort, Soriano‐Navarro, García‐Verdugo, & Izeta, ), and collagen type I hydrogel (Birgit et al, ) to construct a dermis–fat composite. ADSCs cell sheets have been used to construct a three‐layer skin substitute containing subcutaneous fat in vitro without application of scaffold materials (Vidal et al, ); in another study, the dermis and hypodermis were constructed using a silk–collagen hydrogel and silk sponge respectively, and the two layers were then overlapped to form a full‐thickness skin equivalent (Bellas, Seiberg, Garlick, & Kaplan, ).…”
Section: Introductionmentioning
confidence: 99%
“…Vascularization seen in the scaffold is reported to be implemented by enhancing VEGF secretion and promoting vascular endothelial cell migration to the scaffold or differentiating residing stem cells to a vascular phenotype and developing a microvascular network . Fibrin scaffolds and gels have been seeded with both HDF and keratinocytes (capable of forming stratified epithelium with early expression of basement membrane proteins) as well as stem cells (while preserving their differentiation capacity) . Fibrin has also been utilized to prevascularize a dermo‐epidermal skin graft, forming blood and lymphatic capillaries in vitro …”
Section: Natural Biomaterialsmentioning
confidence: 99%
“…Fibrin may have the most beneficial role by acting as a keratinocyte cell delivery scaffold to develop the epidermal layer at the graft site, as fibrin has been shown to be important in epithelialization of the wound through facilitating keratinocyte migration . Its presence in the scaffold as an additive to other biomaterials can harness its specific capacity to promote vascularization in the scaffold.…”
Section: Natural Biomaterialsmentioning
confidence: 99%